Cognitive and affective roles in language and literature learning at the secondary school level (a literature study) - Lustiyantie, Ninuk; Chaeruman, Uwes Anis; Rajaguk-guk, Sastri Br (Eduvest - Journal of Universal Studies, 2025)
Cognitive and affective factors play a crucial role in language learning, influencing the acquisition process and outcomes for learners. The cognitive aspect, such as working memory and metalinguistic awareness, is particularly important in processing and understanding language structures. Additionally, the cognitive load theory suggests that when learners are overwhelmed with information, their language processing abilities are reduced, highlighting the importance of a well-structured learning environment. The research methodology employed in this article is a literature review, involving steps such as topic identification, source gathering, source analysis, classification of findings, synthesis, report writing, and evaluation. The cognitive role in language learning includes various processes, including working memory, cognitive flexibility, attention, metacognition, and cognitive load management. Understanding these cognitive mechanisms is crucial for developing effective language learning strategies and interventions. Furthermore, factors such as self-esteem, language ego, cultural background, emotional involvement, and teacher-student relationships also significantly influence language learning. Therefore, educators must create supportive and engaging learning environments that recognize and respond to students' emotional needs, ultimately facilitating more effective language learning experiences for secondary school students.